The Role of Songs and Singing in the Everyday Practices of the UPA and OUN Soldiers in Zakerzonnia - Prokopov, Vadim; Прокопов, Вадим Юрійович (Дрогобицький державний педагогічний університет імені Івана Франка, 2025)
The purpose of the research is to elucidate and characterize the everyday military practices related to singing and the use of music among the UPA and OUN soldiers in Zakerzonnia region in 1944 – 1947. Research Methodology. The study is based on an interdisciplinary approach that combines the analysis of memoir sources and insurgent documents with theoretical developments in military anthropology, social psychology, and musicology. In the research musicological approaches and concepts have been applied that explain the role of a collective singing in shaping group identity and in combat situations. Scientific Novelty. This article represents the first attempt to explore the anthropological dimension of the use of songs and singing in daily lives of the UPA and OUN soldiers in Zakerzonnia. The research expands the understanding of musical practices in military environments and opens new perspectives for studying the impact of a song on the psychological state and combat effectiveness of military formations. Conclusions. Thus, the role of a song and singing in everyday practices of the UPA and OUN soldiers in Zakerzonnia was multidimensional. The analysis of the sources shows that music served not only an entertainment or emotional function but also acted as a powerful tool for psychological adaptation, group identification, and even tactical influence on the enemy. This study identifies the functions that singing and songs played in the daily lives of the Ukrainian combatants. In particular, singing and songs served as a means of rest and leisure; accompaniment for celebrations and rituals; a tool for unity and communication; emotional support and stress relief; a marker of national identity and the distinction between “us” and “them”; an instrument of ideological influence and propaganda; support in combat situations; and the final act before death. Collective singing contributed to the formation of group identity and the maintenance of morale. Singing practices united combatants and civilians, becoming a kind of ritual that strengthened camaraderie and mutual understanding. Singing played a crucial role in regulating emotional states, alleviating anxiety, and improving mood. The article argues that the phenomenon of “combat singing” was used as a means of influencing the enemy. By analyzing these aspects, we not only gain a deeper understanding of the psychology and culture of the Ukrainian underground but also acquire a broader perspective on the role of music in military conflicts in general. Мета роботи – розкрити і охарактеризувати військові повсякденні практики, пов’язані зі співом пісень і використанням музики, вояків УПА й ОУН на Закерзонні в 1944 – 1947 роках. Методологія дослідження базується на міждисциплінарному підході, що поєднує аналіз мемуарних джерел, повстанських документів із теоретичними напрацюваннями військової антропології, соціальної психології та музикознавства. Дослідження застосовує підходи й концепції музикології, які пояснюють роль колективного співу у формуванні групової ідентичності та в бойових ситуаціях. Наукова новизна. Стаття є першою спробою дослідження антропологічного виміру використання пісень і співу в повсякденному житті вояків УПА й ОУН на Закерзонні. Дослідження розширює уявлення про музичні практики у військовому середовищі й відкриває нові перспективи для вивчення впливу пісні на психологічний стан і бойову ефективність військових формувань. Висновки. Отже, роль пісні та співу в повсякденних практиках вояків УПА й ОУН на Закерзонні мала багатовимірний характер. Аналіз джерел показує, що музика виконувала не лише розважальне чи емоційне завдання, але й була потужним інструментом психологічної адаптації, групової ідентифікації та навіть тактичного впливу на супротивника. У дослідженні виділені функції, які відігравали спів і пісня у повсякденному житті українських комбатантів. Зокрема, це був засіб відпочинку й дозвілля; супровід святкувань та обрядовості; засіб єднання і комунікації; емоційна підтримка й подолання стресу; маркер національної ідентичності й розрізнення “свій” / “чужий”; інструмент ідеологічного впливу та пропаганди; підтримка в бойових ситуаціях; остання практика перед загибеллю. Спільне виконання пісень сприяло формуванню колективної ідентичності й підтримки морального духу. Співочі практики об’єднували комбатантів і цивільне населення, стаючи своєрідним ритуалом, що зміцнював товариські зв’язки та взаєморозуміння. Спів відігравав важливу роль у регулюванні емоційного стану для зняття тривожності й поліпшення настрою. У статті автор доводить, що фактор “бойового співу” використовувався як засіб впливу на ворога. Аналізуючи перелічені аспекти, ми не лише глибше розуміємо психологію та культуру українського підпілля, а й отримуємо ширшу перспективу для ролі музики у військових конфліктах загалом.
Роль пісень і співу в повсякденних практиках вояків УПА й ОУН на Закерзонні
Keywords: Ukrainian Insurgent Army; Українська повстанська армія; Organization of Ukrainian Nationalists; Організація українських націоналістів; Zakerzonnia; Закерзоння; combat singing; бойовий спів; everyday life; повсякдення; military anthropology; військова антропологія